Analysis Of Energy of Heat Pump Heating System with The Environment - O.S.Komilov; S.S.Sayfulloev; Sh.Urinov (Zien Journals, 2021)
The article analyzes the energy generated by the external energy receiver in a heat pump heating system as a result of the system's interaction with the environment until the thermodynamic equilibrium is established, and defines this energy as X energy. The state of this energy is studied in 'lim.
Keywords: X energy; heat pump; condenser; evaporator